Biosynthetic alternatives for corneal transplant surgery. (3rd May 2020) - Griffith, May; Poudel, Bijay Kumar; Malhotra, Kamal; Akla, Naoufal; González-Andrades, Miguel; Courtman, David; Hu, Victor; Alarcon, Emilio I.
ABSTRACT: Introduction: Corneal transplantation surgery faces several fundamental problems, including graft failure, especially in complicated cases, and a marked shortage of human donor corneas. The purpose of this review is to examine several developments in biosynthetic alternatives to donor corneal transplantation. In particular, we focus on the regulatory pathway and considerations needed to design an implant and take it to clinical application. Areas covered: We define biosynthetic implants as those that combine synthetic and natural components, as well as those that mimic materials found in nature. This is a non-comprehensive review of the topic that discusses examples of implants ranging from cell-free devices to those containing cells. We provide a guide to designing implants for clinical application as medical devices, highlighting aspects for consideration at the design and manufacturing stages. Expert opinion: Biosynthetic implants developed as alternatives to conventional corneal transplantation afford customization, particularly for patients at high risk for graft failure. A range of these implants exist, but there appears to be a bottleneck to clinical entry. Implants should be designed with clinical application in mind from the outset to allow for an efficient bench to bedside translation.